Rational play in games: A behavioral approach - Giacomo Bonanno (University of California, Department of Economics, 2021)
We argue in favor of a departure from the standard equilibrium approach in game theory in favor of the less ambitious goal of describing only the actual behavior of rational players. We investigate the notion of rationality in behavioral models of extensive-form games (allowing for imperfect information), where a state is described in terms of a play of the game instead of a strategy profile. The players' beliefs are specified only at reached decision histories and are modeled as pre-choice beliefs, allowing us to carry out the analysis without the need for (objective or subjective) counterfactuals. The analysis is close in spirit to the literature on self-confirming equilibrium, but it does not rely on the notion of strategy. We also provide a characterization of rational play that is compatible with pure-strategy Nash equilibrium.
Keywords: C7; 330; Rationality; extensive-form game; self-confirming equilibrium; Nash equilibrium; behavioral model